Value of Admission HbA1c Level in Non-diabetic Patients With Unstable Angina - Saeed Alipour Parsa; Isa Khaheshi; Mohammad Parsa Mahjoob; Mohammad Ali Akbarzadeh; Shooka Esmaeeli (International Journal of Cardiovascular Practice, 2016)
Introduction: There have been incompatible evidences about the prognostic value of HbA1c on the adverse outcomes in acute coronary syndrome. Also, these data are so limited in nondiabetic patients with unstable angina.Methods: In this cross-sectional study, HbA1c level of 231 nondiabetic patients admitted with unstable angina, was measured using high performance liquid affinity chromatography (HPLC) at admission. Then transthoracic echocardiography (TTE) was performed for evaluation of ejection fraction (EF) using Simpson method.Results: Our data revealed that HbA1c was significantly higher in patients with EF≤ 50% in comparison with EF>50% group (P value=0.01).Conclusions: HbA1c may be a helpful prognostic marker in nondiabetic patients admitted in emergency department with diagnosis of unstable angina.